Perbedaan Hasil Belajar Ipa Dengan Menggunakan Model Pembelajaran Discovery Learning Dan Model Pembelajaran Inkuiri Terbimbing Pada Peserta Didik Kelas Iv Sd Negeri 36 Mataoleo Kabupaten Bombana - Yeyen Sofiana; La Sisi; Chairan Zibar L.Parisu (Prodi PGSD Unsultra, 2021)
This study aims to determine the difference in learning outcomes of fourth-grade students in the Science subject on energy material using the Discovery Learning model and the Guided Inquiry model at SD Negeri 36 Mataoleo. This research is a quasi-experimental study using a 2x2 treatment by level design. The sampling technique used was random sampling, with class IVA as the Discovery Learning group and class IVB as the Guided Inquiry group. Data collection was carried out using multiple-choice tests. The data analysis techniques used in this study included normality tests, homogeneity tests, and hypothesis testing.